2002
DOI: 10.1021/ef0201127
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Spontaneous Imbibition of Water into Oil-Wet Carbonate Reservoir Cores Using a Nonionic and a Cationic Surfactant

Abstract: Some surface-active chemicals are able to improve the spontaneous imbibition of water into oil-wet carbonates. In this work, the oil recovery from oil-wet reservoir cores was compared using aqueous solutions of an ethoxylated alcohol (EA) and a cationic surfactant (C12TAB). The experiments were conducted at room temperature using short (∼5 cm) and long (∼30 cm) cores with initial water saturation in the range of 17-33%. Due to wide variation in porous structure, the cores were characterized into two groups, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(103 citation statements)
references
References 16 publications
3
98
0
Order By: Relevance
“…25;31 Several researchers reported that dilute solutions of chemical surfactants can alter the wettability of carbonate rock toward a more waterwet state. [6][7][8][9][10][11][12][13] This wettability change can improve oil recovery in fractured carbonate reservoirs by accelerating the spontaneous imbibition process during water flooding. They also reported that surfactant loss due to adsorption and/or retention on reservoir rock can be significant even at dilute surfactant concentrations.…”
Section: Evaluate the Biosurfactants For Improved Oil Recovery In Framentioning
confidence: 99%
See 1 more Smart Citation
“…25;31 Several researchers reported that dilute solutions of chemical surfactants can alter the wettability of carbonate rock toward a more waterwet state. [6][7][8][9][10][11][12][13] This wettability change can improve oil recovery in fractured carbonate reservoirs by accelerating the spontaneous imbibition process during water flooding. They also reported that surfactant loss due to adsorption and/or retention on reservoir rock can be significant even at dilute surfactant concentrations.…”
Section: Evaluate the Biosurfactants For Improved Oil Recovery In Framentioning
confidence: 99%
“…Several studies revealed that the injection of dilute surfactants into oil reservoirs could also modify the wettability of the reservoir rock. [6][7][8][9][10][11][12][13] This phenomenon can be very useful in fractured carbonate reservoirs where the wettability change can improve oil recovery by accelerating the spontaneous imbibition process. 14;15 The overall objective of this project is to evaluate the use of low-cost biosurfactants produced from agriculture process waste streams to improve oil recovery in fractured carbonate reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic surfactant has been used to alter wettability of carbonate formations to more water-wet conditions [1][2][3][4][5] . Standnes and Austad proposed the mechanism to be the formation of ion-pairs between surfactant monomers and the adsorbed carboxylates 1 .…”
Section: Taskmentioning
confidence: 99%
“…Application of surfactants to alter wettability and thus enhance spontaneous imbibition has been investigated by Austad, et al [7][8][9][10][11] with chalk and dolomite cores. Chen, et al 12 , investigated enhanced spontaneous imbibition with nonionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Spinler, et al 13 , evaluated 46 surfactants for enhanced spontaneous imbibition in chalk formations. Standnes, et al 11 and Chen, et al 12 used either nonionic or cationic surfactant with a strategy to alter wettability but avoid ultra-low tensions. The work presented here differs from the previous work in that sodium carbonate and anionic surfactants are used to both alter wettability and reduce interfacial tension to ultra-low values.…”
Section: Introductionmentioning
confidence: 99%